Epidemiological and Clinical Characterization of Superinfections in Critically Ill Coronavirus Disease 2019 Patients. (11th June 2021) - Signorini, Liana; Moioli, Giovanni; Calza, Stefano; Van Hauwermeiren, Evelyn; Lorenzotti, Silvia; Del Fabro, Giovanni; Renisi, Giulia; Lanza, Paola; Saccani, Barbara; Zambolin, Giulia; Latronico, Nicola; Castelli, Francesco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To describe the epidemiology of superinfections (occurring > 48 hr after hospital admission) and their impact on the ICU and 28-day mortality in patients with coronavirus disease 2019 with acute respiratory distress syndrome, requiring mechanical ventilation. DESIGN: Retrospective analysis of prospectively collected observational data. SETTING: University-affiliated adult ICU. PATIENTS: Ninety-two coronavirus disease 2019 patients admitted to the ICU from February 21, 2020, to May 6, 2020. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: The prevalence of superinfection at ICU admission was 21.7%, and 53 patients (57.6%) had at least one superinfection during ICU stay, with a total of 75 (82%) ventilator-associated pneumonia and 57 (62%) systemic infections. The most common pathogens responsible for ventilator-associated pneumonia were Pseudomonas aeruginosa ( n = 26, 34.7%) and Stenotrophomonas maltophilia ( n = 14, 18.7%). Bloodstream infection occurred in 16 cases, including methicillin-resistant Staphylococcus epidermidis ( n = 8, 14.0%), Enterococcus species ( n = 6, 10.5%), and Streptococcus species ( n = 2, 3.5%). Fungal infections occurred in 41 cases, including 36 probable (30 by Candida albicans, six by C. nonalbicans ) and five proven invasive candidiasis (three C. albicans, two C. nonalbicans ). Presence of bacterial infections (odds ratio, 10.53; 95% CI, 2.31–63.42; p = 0.005), age (odds ratio, 1.17; 95% CI, 1.07–1.31; p = 0.001), and the highest Sequential Organ Failure Assessment score (odds ratio, 1.27; 95% CI, 1.06–1.63; p = 0.032) were independently associated with ICU or 28-day mortality. CONCLUSIONS: Prevalence of superinfections in coronavirus disease 2019 patients requiring mechanical ventilation was high in this series, and bacterial superinfections were independently associated with ICU or 28-day mortality (whichever comes first).